Impact Assessment on Mental Rehabilitation Programs during the Post-Conflict Arab Spring Period - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (STIKES Columbia Asia Medan, 2025)
This study systematically evaluates the effectiveness of mental rehabilitation programs implemented for post-conflict populations in the aftermath of the Arab Spring. A meta-analytical approach was applied to 47 empirical studies encompassing 12,873 participants across five affected countries, Egypt, Tunisia, Libya, Yemen, and Syria, from 2012 to 2023. The analysis reveals a significant reduction in symptoms of Post-Traumatic Stress Disorder (PTSD) (d = -0.78, 95% CI [-0.92, -0.64], p < .001) and depression (d = -0.65, 95% CI [-0.79, -0.51], p < .001) following psychological intervention. Among the various therapeutic modalities, Cognitive Behavioral Therapy (CBT) exhibited the strongest effect (g = 0.89), followed by Narrative Exposure Therapy (g = 0.76) and Eye Movement Desensitization and Reprocessing (g = 0.71). Analysis of moderating variables demonstrated that both program duration (β = 0.31, p < .01) and family involvement (β = 0.28, p < .01) significantly contributed to enhancing the efficacy of the intervention. These findings advance the understanding beyond previous research by Bwirire et al. (2022) and Eskici et al. (2023), which were constrained to short-term outcomes. This study confirms that therapeutic gains may persist up to two years post-intervention (r = 0.67, p < .001). Moreover, the results underscore combining community-based interventions with individualized therapy yields more favorable outcomes than the one-dimensional strategies reviewed in earlier literature.